A Review on Ruta graveolens L. Its Usage in Traditional Medicine and Modern Research Data - Z Naghibi Harat; M Kamalinejad; MR Sadeghi; HR Sadeghipour; MR Eshraghian (Institue of Medicinal Plants, ACECR, 2009)
According to manuscripts, Ruta (rue) was one of the plants which had been abundantly used for prevention and treatment of diseases, both in Iranian and nation's Traditional medicine(TM). Natives are still using this plant through the world. Clinical and experimental modern trials had shown the anti-inflammatory, anticancer, antiarrhytmic, anti-hypertensive, antimicrobial, antifungal, contraceptive and abortive effects of this plant in addition to some central nervous system effects. Almost all of these were mentioned in TM besides a couple of other effects which there were no experimental data about them in modern researches. In other hand, rue contains so many chemicals and complex compounds which their exact effects and mechanism of actions are still not well known. Besides there are some data about toxic effects of rue but there is no reliable toxicological study which could explain the side effects, toxic dosage or detoxification methods. In this review we explain about this plant, its usage in TM and the results of different modern trials and give a plenty of experimental view of points which could be done in future.